Gender as a moderation of destination brand experiences - Miska Irani Tarigan; Errie Margery; Betniar Purba (Institute of Computer Science (IOCS), 2023)
Following the pandemic, the tourism industry reopened and made strategic efforts to bring domestic and foreign tourists to Indonesia's top destinations. One of the priority national priority strategic areas is the Lake Toba tourist area. In addition to applying experiential marketing to the series during a visit to the destination, the initial strategy in this research is to create brand loyalty to the destination in the Lake Toba tourist area. The gander is used as an intervening variable in determining the destination brand experience, with the ultimate goal of forming destination brand loyalty. By understanding the role of the destination image in the formation of the destination brand experience; infrastructure and supporting services or attractions at destinations that are expected to shape destination brand loyalty in the Lake Toba tourist area. This study used purposive and quota sampling on domestic tourists, and the participants included 200 people. The data was processed using SmartPLS, and the findings indicated that gender can moderate destination attractions on destination brand experiences. Meanwhile, gender cannot moderate the impact of the destination image variable, as well as the infrastructure and support service variables, on the destination brand experience. The findings of this study can be used to identify interesting attractions in destinatios that are expected to increase tourist visits to the Lake Toba Tourism Area.